Certificate of Land Rights in the Legal Philosophy of Notary - Saptomo, Prof. Dr. Ade; Sihombing, Dr. B. F. (International Journal of Scientific Research and Management (IJSRM), 2020)
This study aims to analyze the legal issues faced with regard to society and land, birth certificates and legal reviews of the role and duties of a notary in Indonesia. The method in this research is to use normative legal research, collect and analyze secondary data, namely books, diaries, laws and regulations, court decisions, legal theories and opinions of leading legal scholars who to analyze statutory regulations and various literatures related to land title certificates. The results of the study found that the importance of land title certificates, as a person's control over land, is a human right that deserves protection and assurance of certainty of ownership and is contained in a rule as regulated in UUPA No. 5 of 1960. Then, the role of a notary as an official which is given the authority by the state, especially the making of authentic deeds, as regulated in UUJN No. 30 of 2004, the Notary Public needs to use a legal philosophy approach to ensure legal protection for the community using his services through accurate case mapping, legal corrections, linguistic improvements and comprehensive services.